Bisphenol-A induced oxidative stress, inflammatory gene expression, and metabolic and histopathological changes in male Wistar albino rats: protective role of boron. Issue 2 (23rd January 2019) - Acaroz, Ulas; Ince, Sinan; Arslan-Acaroz, Damla; Gurler, Zeki; Demirel, Hasan Huseyin; Kucukkurt, Ismail; Eryavuz, Abdullah; Kara, Recep; Varol, Nuray; Zhu, Kui
Graphical Abstract: Abstract: Bisphenol A (BPA) is one of the most produced chemicals in the world and has been widely employed in the food industry. Continuous and widespread exposure to BPA through drinking water and food leads to health concerns for humans. This study evaluated the effects of boron (B) on BPA-mediated oxidative stress in male Wistar albino rats. Rats were equally divided into 5 groups; corn oil was given orally to the control group; 25 mg kg −1 of BPA dissolved in corn oil was given orally to the second group. All other groups received the same dose of BPA and different doses of B (5, 10, and 20 mg kg −1 per day, respectively) orally for 30 days. The administration of BPA significantly decreased glutathione levels and increased malondialdehyde levels in rat tissues. Furthermore, BPA treatment reduced the catalase and superoxide dismutase activities in tissues and erythrocytes. Also, mRNA expression levels of TNF-α, IL-1β, and IL-6 in the brain, liver, and testes of rats were augmented, whereas IL-10 was decreased with BPA treatment. Besides, BPA treatment adversely altered biochemical parameters and caused damage to the cell integrity of rat tissues. However, B administration reversed BPA-induced alterations in rat tissues in a dose-dependent manner. Furthermore, B exhibited antioxidant and anti-inflammatory effects and regulated metabolic and histopathological alterations in male Wistar albino rats exposed to BPA.